13C‐NMR, 13C‐13C gCOSY, and ESI‐MS characterization of ether‐bridged condensation products in N, N′‐dimethylurea‐formaldehyde systems1. Issue 6 (16th October 2012) - Kibrik, Éléonore J.; Steinhof, Oliver; Scherr, Günter; Thiel, Werner R.; Hasse, Hans
Abstract The reaction of urea with formaldehyde is the basis for the production of urea‐formaldehyde (UF) resins which are widely applied in the wood industry. The presence of ether‐bridged condensation products in the UF resin reaction system is an open question in the literature. It is addressed in the present work. The N, N′‐dimethylurea‐formaldehyde model system was studied since it is chemically similar to the UF resin reaction system but allows for a simple elucidation of all reaction products. It was analyzed by 13C‐NMR spectroscopy and ESI‐MS. In corresponding NMR and MS spectra, peaks due to methoxymethylenebis(dimethyl)urea and its hemiformal were observed. 13C‐13C gCOSY analysis was conducted using labeled 13C‐formaldehyde. The correlation spectra showed evidence for an ether‐bridged compound and mass spectra exhibited peaks agreeing with labeled methoxymethylenebis(dimethyl)urea and its hemiformal. Methoxymethylenebis(dimethyl)urea was characterized in N, N′‐dimethylurea‐formaldehyde systems in acidic and slightly basic media. As urea is very similar to N, N′‐dimethylurea, the results of this work strengthen the assumption that ether‐bridged condensation products are likely to form in UF resins. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013